2x-5+(3x+4)=5x-1

Simple and best practice solution for 2x-5+(3x+4)=5x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-5+(3x+4)=5x-1 equation:


Simplifying
2x + -5 + (3x + 4) = 5x + -1

Reorder the terms:
2x + -5 + (4 + 3x) = 5x + -1

Remove parenthesis around (4 + 3x)
2x + -5 + 4 + 3x = 5x + -1

Reorder the terms:
-5 + 4 + 2x + 3x = 5x + -1

Combine like terms: -5 + 4 = -1
-1 + 2x + 3x = 5x + -1

Combine like terms: 2x + 3x = 5x
-1 + 5x = 5x + -1

Reorder the terms:
-1 + 5x = -1 + 5x

Add '1' to each side of the equation.
-1 + 1 + 5x = -1 + 1 + 5x

Combine like terms: -1 + 1 = 0
0 + 5x = -1 + 1 + 5x
5x = -1 + 1 + 5x

Combine like terms: -1 + 1 = 0
5x = 0 + 5x
5x = 5x

Add '-5x' to each side of the equation.
5x + -5x = 5x + -5x

Combine like terms: 5x + -5x = 0
0 = 5x + -5x

Combine like terms: 5x + -5x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| -16+-3x-16= | | -8x+4x-24=-28 | | 3-t/23+5=12 | | 4/3*(3.14)*1^3 | | 0.2-0.4x^2=-2 | | X^3-10X^2+34x=0 | | 7(a+4)=7(a-2) | | -7n-4+5=22 | | 4/3(3.14)1 | | f(x)=x^2-5x-14 | | 4x+8=2+20 | | 5(3+6x)-3=102 | | 31-12x=221 | | 4x^2+11x-25=0 | | 6x^2+11x-2x=0 | | 3/5k^2-10/3=0 | | 5x+4y=55 | | 15/x+3 | | 0.17y+0.04(y+4000)=1840 | | -4y+7=5y+2 | | (12.8)(4.1)= | | 0.01x+0.10x+0.25x(26-2x)=1.82 | | 7x^2-3x+0=0 | | 18-2p=3+p | | -x+3+10x=-2+4x+10 | | 3x+1=41 | | 31=4t+3 | | x-x^2-x^3=0 | | -x^2=-3x+5 | | 750-50*24= | | -11/t=8/48 | | -3p+8=6-(8p+5) |

Equations solver categories